A New Thiolate‐Bound Dimanganese Cluster as a Structural and Functional Model for Class Ib Ribonucleotide Reductases. Issue 12 (14th February 2023) - Battistella, Beatrice; Lohmiller, Thomas; Cula, Beatrice; Hildebrandt, Peter; Kuhlmann, Uwe; Dau, Holger; Mebs, Stefan; Ray, Kallol
Abstract: In class Ib ribonucleotide reductases (RNRs) a dimanganese(II) cluster activates superoxide (O2 ⋅ − ) rather than dioxygen (O2 ), to access a high valent Mn III −O2 −Mn IV species, responsible for the oxidation of tyrosine to tyrosyl radical. In a biomimetic approach, we report the synthesis of a thiolate‐bound dimanganese complex [Mn II 2 (BPMT)(OAc)2 ](ClO)4 (BPMT=(2, 6‐bis{[bis(2‐pyridylmethyl)amino]methyl}‐4‐methylthiophenolate) (1 ) and its reaction with O2 ⋅ − to form a [(BPMT)MnO2 Mn] 2+ complex 2 . Resonance Raman investigation revealed the presence of an O−O bond in 2, while EPR analysis displayed a 16‐line S t =1/2 signal at g =2 typically associated with a Mn III Mn IV core, as detected in class Ib RNRs. Unlike all other previously reported Mn−O2 −Mn complexes, generated by O2 ⋅ − activation at Mn2 centers, 2 proved to be a capable electrophilic oxidant in aldehyde deformylation and phenol oxidation reactions, rendering it one of the best structural and functional models for class Ib RNRs. Abstract : With the aim to mimic the reactivity of class Ib ribonucleotide reductases (RNRs), a new thiolate‐bound Mn II 2 compound was studied. Upon superoxide activation it forms a reactive intermediate that exhibits a 16‐line S t =1/2 EPR signal at g =2 and oxidizes substituted phenols, thereby resembling the enzymatic behavior and, thus, providing new mechanistic insight into class Ib RNR reactivity.